Polymeric Nanoneedle Arrays Mediate Stiffness‐Independent Intracellular Delivery (Adv. Funct. Mater. 3/2022). (14th January 2022) - Yoh, Hao Zhe; Chen, Yaping; Aslanoglou, Stella; Wong, Sherman; Trifunovic, Zlatan; Crawford, Simon; Lestrell, Esther; Priest, Craig; Alba, Maria; Thissen, Helmut; Voelcker, Nicolas H.; Elnathan, Roey
Abstract : Polymeric Nanoneedle Arrays In article number 2104828, Yaping Chen, Nicolas H. Voelcker, Roey Elnathan, and co‐workers demonstrate the fabrication of relatively low‐cost and high throughput polymeric nanoneedles from cell culture polystyrene. The nanoneedles with precise geometry are imprinted directly on polystyrene from the cell culture petri dish via nanoimprint lithography. The nanoneedles arrays can precisely manipulate cellular processes and mediate intracellular delivery in mammalian cells. This presents opportunities for novel integration of nanostructures into traditional polymeric cell cultureware.